Odpowiedzi

Najlepsza Odpowiedź!
  • Użytkownik Zadane
2010-02-15T17:22:53+01:00

b)(x-2)(x+5)(2x-1)=( x²+5x-2x-10)(2x-1)=(x²+3x-10)(2x-1)= 2x³+6x²-20x-x²-3x+10=2x³-5x²-23x+10
c)(x-4)(x+1)²=(x-4)(x²+2x+1)=x³+2x²+x-4x²-8x-4=x³-2x²-7x-4
d)(2x-3)²(x+2)=(4x²-12x+9)(x+2)=4x³+8x²-12x²-24x+9x+18= 4x³-4x²-15x+18
18 3 18
2010-02-15T17:23:56+01:00
B)(x-2)(x+5)(2x-1)=(x²+5x-2x-10)(2x-1)=
=2x³-x²+10x²-5x-4x²+2x-20x+10=
=2x³-x²+10x²-4x²-5x+2x-20x+10=2x³+5x²-23x+10
c)(x-4)(x+1)²=(x-4)(x²+2x+1)=x³+2x²+x-4x²-8x-4=
=x³+2x²-4x²+x-8x-4=x³-2x²-7x-4
d)(2x-3)²(x+2)=(4x²-12x+9)(x+2)=
=4x³+8x²-12x²-24x+9x+18=4x³-4x²-15x+18
12 4 12